2017
DOI: 10.1080/00207179.2017.1404130
|View full text |Cite
|
Sign up to set email alerts
|

A globally exponentially stable speed observer for a class of mechanical systems: experimental and simulation comparison with high-gain and sliding mode designs

Abstract: It is shown in the paper that the problem of speed observation for mechanical systems that are partially linearisable via coordinate changes admits a very simple and robust (exponentially stable) solution with a Luenberger-like observer. This result should be contrasted with the very complicated observers based on immersion and invariance reported in the literature. A second contribution of the paper is to compare, via realistic simulations and highly detailed experiments, the performance of the proposed obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…The drawback of this approach is that it is based on the linearization of the system, and therefore it is not valid when the angle θ is not close to the desired position and the approximation sin(θ) ≈ θ does not hold. This drawback can be alleviated using linear observers with time-varying gains, e.g., with gains scheduling, or using nonlinear state observers for mechanical systems, see [10] and the references therein. However, such solutions are typically harder to design and implement.…”
Section: Finite Time Velocity Observermentioning
confidence: 99%
See 3 more Smart Citations
“…The drawback of this approach is that it is based on the linearization of the system, and therefore it is not valid when the angle θ is not close to the desired position and the approximation sin(θ) ≈ θ does not hold. This drawback can be alleviated using linear observers with time-varying gains, e.g., with gains scheduling, or using nonlinear state observers for mechanical systems, see [10] and the references therein. However, such solutions are typically harder to design and implement.…”
Section: Finite Time Velocity Observermentioning
confidence: 99%
“…It can be shown that the control law (8) with the finite-time observers (10) and (12) locally stabilizes the system (1). Indeed, for the observers (10) and (12) there exists the common settling time T com = T (e p (0), e r (0)), such that the control laws (5) and 8are equivalent for t ≥ T com . Since the control law (5) is stabilizing for the linearized system (4), it is locally stabilizing for the nonlinear system (1) in a neighborhood of the desired equilibrium; define this neighborhood as α .…”
Section: Closed-loop System Behavior Under Biased Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CMG for inverted pendulum balancing has been intensively studied in recent years. In work [6] there was suggested a global change of coordinates to transform the dynamics of the system into a lower nonlinear subsystem and stabilize the system with a control Lyapunov function. Another research [7] was devoted to creation of a model predictive controller (MPC) to control such a system.…”
Section: Introductionmentioning
confidence: 99%